Anatomic Risk Factors for Osteochondral Fracture of Acute First-Time Patellar Dislocation in Adolescents: A Retrospective Magnetic Resonance Imaging Study. (8th August 2022) - Li, Junran; Chen, Chuanjie; Zhou, Hongyan; Zhai, Jingxiu; Zhao, Hongbo; Li, Ligeng
Abstract : Objective . To analyze the risk factors for osteochondral fracture (OCF) of first-time acute patellar dislocation (APD) through measurements of patellofemoral anatomy in adolescents. Methods . In this prospective study, all patients were divided into two groups according to whether OCF was detected on magnetic resonance imaging (MRI): Group A (associated with OCF) and Group B (without OCF). Patellofemoral anatomy was evaluated with four aspects including trochlear/patellar dysplasia, patella location, patellofemoral matching, and morphologic classification. On MRI scans, trochlear facet asymmetry ratio (TFAR), lateral trochlear inclination (LTI), sulcus angle (SA), trochlear depth (TD), and patellar depth (PD) were measured to assess trochlear/patellar dysplasia. Insall–Salvati index (ISI), Caton–Deschamps index (CDI), Blackburne–Peel index (BPI), lateral patellofemoral angle (LPFA), patellar tilt angle (PTA), and lateral patellar displacement (LPD) were measured to show the location of patella. Patellofemoral matching was analyzed through the measurements of patellofemoral congruence angle (PFCA), patellofemoral index (PFI), and patellotrochlear index (PTI). Results . A total of ninety-four adolescents from 49 boys and 45 girls (mean age, 15 years; range, 10–18 years) with first-time APD were recruited and included in Group A (65) and Group B (29). The PFI (2.62 ± 0.51 vs . 2.10 ± 0.44) and PTI (0.28 ± 0.05 vs . 0.22 ± 0.07) were significantly higher in Group B than Group A P < 0.05 . There were no significant differences in other quantitative outcomes of the two groups P > 0.05 . The distribution of Dejour/Wiberg classification was statistically similar between the two groups P > 0.05 . Conclusions . Adolescent patients with first-time APD complicating OCF have closer morphologic features of patellofemoral dysplasia and patella location when compared to adolescents without OCF. Abnormal patellofemoral matching increases the risk of OCF after first-time APD in adolescents.